The Flavonoid Components of Scutellaria baicalensis: Biopharmaceutical Properties and their Improvement using Nanoformulation Techniques - Wang, Jilin; Feng, Xiaojiao; Li, Ziwei; Liu, Yiting; Yang, Wenzhuo; Zhang, Tingen; Guo, Pan; Liu, Zhidong; Qi, Dongli; Pi, Jiaxin (Current Topics in Medicinal Chemistry, 2023)
Scutellaria baicalensis georgi, known as “Huangqin” in its dried root form, is a herb widely used in traditional Chinese medicine for “clearing away heat, removing dampness, purging fire and detoxification”. Baicalin, baicalein, wogonin, and wogonoside are the main flavonoid compounds found in Scutellaria baicalensis. Scutellaria baicalensis flavonoid components have the potential to prevent and treat a host of diseases. The components of S. baicalensis have limited clinical application due to their low water solubility, poor permeability, and microbial transformation in vivo. Nanopharmaceutical techniques can improve their biopharmaceutical properties, enhance their absorption in vivo, and improve their bioavailability. However, due to the limited number of clinical trials, doubts remain about their toxicity and improvements in human absorption as a result of nanoformulations. This review summarizes the latest and most comprehensive information regarding the absorption, distribution, metabolism, and excretion of the Scutellaria baicalensis components in vivo. We examined the main advantages of nanodrug delivery systems and collected detailed information on the nanosystem delivery of the Scutellaria baicalensis components, including nanosuspensions and various lipid-based nanosystems. Lipid-based systems including liposomes, solid lipid nanoparticles, nanoemulsions, and self-micro emulsifying drug delivery systems are introduced in detail. In addition, we make recommendations for related and future research directions. Future research should further examine the absorption mechanisms and metabolic pathways of nanoformulations of the components of Scutellaria baicalensis in vivo, and accurately track the in vivo behavior of these drug delivery systems to discover the specific reasons for the enhanced bioavailability of nanoformulations of the scutellaria baicalensis components. The development of targeted oral administration of intact nanoparticles of Scutellaria baicalensis components is an exciting prospect.
Keywords: Baicalein